2003
DOI: 10.1542/peds.112.6.1321
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Television Viewing Patterns on Fruit and Vegetable Consumption Among Adolescents

Abstract: Television viewing is inversely associated with intake of fruit and vegetables among adolescents. These associations may be a result of the replacement of fruits and vegetables in youths' diets by foods highly advertised on television.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
134
0
13

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(168 citation statements)
references
References 40 publications
18
134
0
13
Order By: Relevance
“…Twenty-five dietary behaviors were identified, and for brevity dietary behaviors that were studied most often and dietary behaviors that are important in their contribution to the healthfulness of overall diet were tabulated (Table 3). There were five longitudinal studies (nine independent samples) assessing the association between sedentary behavior and dietary intake in children; 23,26,28,33,38 three out of these five studies scored higher than the median score for study quality (median =8/16), corroborating the results found from cross-sectional studies showing that TV viewing was inversely associated with fruit and vegetable consumption, 23 and positively associated with total energy intake, 26,28 energy-dense drinks, snacks and fast foods. 28 Overall, therefore, sedentary behavior in children appears to be clearly associated with elements of a less healthy diet.…”
Section: Associations Between Sedentary Behavior and Diet In Childrensupporting
confidence: 68%
See 1 more Smart Citation
“…Twenty-five dietary behaviors were identified, and for brevity dietary behaviors that were studied most often and dietary behaviors that are important in their contribution to the healthfulness of overall diet were tabulated (Table 3). There were five longitudinal studies (nine independent samples) assessing the association between sedentary behavior and dietary intake in children; 23,26,28,33,38 three out of these five studies scored higher than the median score for study quality (median =8/16), corroborating the results found from cross-sectional studies showing that TV viewing was inversely associated with fruit and vegetable consumption, 23 and positively associated with total energy intake, 26,28 energy-dense drinks, snacks and fast foods. 28 Overall, therefore, sedentary behavior in children appears to be clearly associated with elements of a less healthy diet.…”
Section: Associations Between Sedentary Behavior and Diet In Childrensupporting
confidence: 68%
“…Television viewing was positively associated with fast food consumption in seven samples and not associated in one. Television viewing was positively associated with energy-dense drinks in seven out of seven samples, positively associated with total energy intake in eight of eleven samples, and positively associated with percentage energy from fat in two out of two samples.There were five longitudinal studies (nine independent samples) assessing the association between sedentary behavior and dietary intake in children; 23,26,28,33, 38 three out of these five studies scored higher than the median score for study quality (median =8/16), corroborating the results found from cross-sectional studies showing that TV viewing was inversely associated with fruit and vegetable consumption, 23 and positively associated with total energy intake, 26, 28 energy-dense drinks, snacks and fast foods. 28 Overall, therefore, sedentary behavior in children appears to be clearly associated with elements of a less healthy diet.…”
mentioning
confidence: 99%
“…There is a consensus that the time spent on social networking is positively associated with the consumption of unhealthy foods, which is also consistent with research carried out by Boynton--Jarret et al 15 . These authors evaluated adolescents over a period of 19 months and found an inverse relationship between the time spent watching television and the intake of fruits and vegetables.…”
Section: Discussionsupporting
confidence: 88%
“…Essa associação entre menor faixa etária e maior tempo gasto assistindo TV também foi demonstrada por Eisenman et al (9) Estudos confirmaram que a inatividade física na infância transpõe para a adolescência (22) e dessa para a vida adulta (23) . Sendo assim, quanto mais cedo houver intervenções para reduzir o sedentarismo menor a probabilidade do desenvolvimento de obesidade na adolescência e consequentemente menor risco para as doenças crônicas na vida adulta.…”
Section: Resultsunclassified